2018
DOI: 10.3390/ijms19082171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BMP-2 Enhances the Osteoblast Differentiation of Human Amnion Mesenchymal Stem Cells Seeded on Nano-Hydroxyapatite/Collagen/Poly(l-Lactide)

Abstract: Background: The aim of this study is to evaluate the effects of recombinant human bone morphogenetic protein 2 (rhBMP-2), human amnion mesenchymal stem cells (hAMSCs), and nanohydroxyapatite/collagen/poly(l-lactide) (nHAC/PLA) in tissue engineering to provide potential approaches for periodontal bone regeneration. Methods: hAMSCs were isolated from discarded amniotic membrane samples and cultured in vitro. Alkaline phosphatase (ALP) staining and alizarin red staining were performed to evaluate the osteoblast (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 48 publications
3
48
0
1
Order By: Relevance
“…Epigenetic analyses carried out in 84 genes of the osteogenetic pathway, in hASCs grown on biomaterial, indicate that among DEGs BMP2 is induced and upregulated. Accumulating studies proved that BMP‐2 is involved in bone formation, bone remodeling, bone development, and osteoblast differentiation . BMP‐2, belonging to the BMPs family, is a potent osteoinductive cytokine from the transforming growth factor beta (TGF‐β) family, and it is currently the most commonly used protein‐based bone graft substitute .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Epigenetic analyses carried out in 84 genes of the osteogenetic pathway, in hASCs grown on biomaterial, indicate that among DEGs BMP2 is induced and upregulated. Accumulating studies proved that BMP‐2 is involved in bone formation, bone remodeling, bone development, and osteoblast differentiation . BMP‐2, belonging to the BMPs family, is a potent osteoinductive cytokine from the transforming growth factor beta (TGF‐β) family, and it is currently the most commonly used protein‐based bone graft substitute .…”
Section: Discussionmentioning
confidence: 99%
“…BMP‐2, belonging to the BMPs family, is a potent osteoinductive cytokine from the transforming growth factor beta (TGF‐β) family, and it is currently the most commonly used protein‐based bone graft substitute . Recombinant human bone morphogenetic protein 2 (rhBMP‐2), in human amnion MSCs, with nano‐HA/Coll/poly ( l ‐lactide), provides a potential approaches in tissue engineering for periodontal bone regeneration . Furthermore, in vitro and in vivo results using a rat cranial bone defect model demonstrated that the 3D nanofibrous scaffolds incorporated with nano‐hydroxylapatite (nHA) and BMP‐2 peptides exhibited favorable biocompatibility and osteoinductivity .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 2.14 | Statistical analysis Statistical analysis was performed using SPSS 21.0 Software (IBM Corp. Armonk, NY). After 24 hours of culture, cells were treated with trypsin and centrifuged at 157g for 5 minutes, and resuspended with PBS containing 3% penicillin.…”
Section: Ectopic Osteogenesismentioning
confidence: 99%